(3GdeJWdHGJ hGdHOGFd hGdNHQGJs - (3cSjOR(B, (3cQjSJjfs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B,s, 1997)
(3GdEWGQ dJMdjd JQJjHGJ GdeDSSI aj GdHfjI GdGSGSjI(B- (3NHQGJ eSJaGOI ef JQJjHGJ eDSSI HOjdI(B- (3GTJQGWGJ dVeGf aGYdjI GdJQJjHGJ GdeDSSjI(B.s
Keywords: (3GdESJKeGQGJ GdMchejIs; (3Jehjds; (3NUNUI GdeTQhYGJs